PENATALAKSANAAN FISIOTERAPI PADA KASUS TRIGGER FINGER DEXTRA DENGAN MENGGUNAKAN MODALITAS ULTRASOUND, MASSAGE DAN HOLD RELAX DI RSU PINDAD KOTA BANDUNG - Tasya Zulfalina; Ika Rahman (LPPM Sekolah Tinggi Ilmu Kesehatan Siti Hajar Medan, 2021)
Trigger Finger is a common disorder that is characterize by an irreversibility the bent finger and assocated with dysfunction and oan caused by thickening of a flexor tendon, in combination with thickening of the tendon sheath in the same place.To find out the management of physiotherapy in reducing pain, increasing the range of motion of joints in Trigger Finger sufferers with Ultrasound, Massage and exercise therapy in the form of hold relax.After doing physiotherapy six times, result of the assessment pain dexreased from T1: 8 to T6: 4, motion pain from T1: 6 to T6: 2, increased value of flexor muscle strength from T1: 3 to T6:5, increased strength of extensor muscle from T1:3 to T6: 5, increased flecion range of motion of proxs interphaangsl joint dextra from T1:112o to T6:115:o. Ultrasound , massage and hold relax can help reduce pain, increase muscle and increase range of motion in cases of Trigger Finger